Waste Separation from Sea by using Smart Boat - K. Hari Krishna, A. Sirisha, V. Madhav Reddy (Mathematical Statistician and Engineering Applications, 2021)
Water, which has been severely polluted, is a key resource for human survival. We have contributed to creating a small prototype for removing waste from water, whether it be sea or river, in order to save the pure water for humanity. The project’s primary goal is to limit the use of plastic, chemicals, and other harmful substances, especially in waterways. In this project, the locomotive part is controlled by NodeMCU, which serves as the controller. The net that connects the left and right motors using L298N motor drivers makes up the locomotive portion. The motors employed will determine the direction of the overall movement.The mobile device on which the programme is loaded determines the direction. The NodeMCU and Blynk applications are utilised for communication. which in turn manages the intelligent boat. A tiny water tank filled with plastic, Thermocol, and other floating materials is used to test the prototype. Here, a servo motor that is controlled by PWM was used. It operates using the PWM (Pulse with Modulation) that the control wires supply. Remove the plastic and solid from above the river to solve this issue. Here, the belt is fixed and the waste picker is attached to the boat. The garbage picker scoops up the trash on the water while driving the boat by spinning the belt. We use a phone to control the direction.